Base-mediated direct fluoroalkenylation of 2-phenyl-1, 3, 4-oxadiazole, benzothiazole and benzoxazole with gem-difluoroalkenes1. Issue 11 (7th February 2015) - Zhang, Xuxue; Lin, Yingyin; Zhang, Juan; Cao, Song
<x xml:space="preserve">Abstract</x> Direct α-fluorovinylation of 2-phenyl-1, 3, 4-oxadiazole, benzothiazole and benzoxazole with gem-difluoroalkenes under the assistance of KHMDS or NaH at room temperature was developed.